(untitled) (Bangladesh Journal of Botany, 2021)
Experiments were conducted to identify suitable agro-morphological indicators of salinity tolerance and to classify fifty mungbean accessions into different salt tolerant groups by screening under different NaCl solution in pot culture in green house condition for two growing seasons. Results reveled that the early growth phase of mungbean is highly affected due to salinity and the interrelationship between salinity and accessions was also statistically significant for yield parameters under different levels of salinity stress. Salt tolerant accessions were less affected at high salinity and could be produced better total dry matter as compared to others. On the basis of relative total dry matter (RTDM%), accessions were categorized as highly tolerant, moderately susceptible and highly susceptible. G4 was found to be the best tolerant line after considering both the seasons and all the tested parameters. Correlation study suggested that germination was least affected while seedling length, pod and seed yield severely fractured due to salinity. These desirable parameters may take part in future breeding programme as salinity indicators and also by getting introduced into the susceptible lines, whereas, the tolerant accessions can be introduced as tolerant checks. Bangladesh J. Bot. 50(3): 475-482, 2021 (September)